Genetic and peripheral markers of the oxytocin system and parental care jointly support the cross-generational transmission of bonding across three generations. (April 2019) - Fujiwara, Takeo; Weisman, Omri; Ochi, Manami; Shirai, Kokoro; Matsumoto, Kenji; Noguchi, Emiko; Feldman, Ruth
Highlights: No study has tested the joint contribution of oxytocin, oxytocin related SNPs and parental care across three generations. Mothers experienced overprotective parenting exhibited more rejection to their infants when carrying OXTRrs53576 G allele. Infants who were OXTRrs2254298 A carriers whose mothers reported more bonding to their infants had higher oxytocin levels. Abstract: Background: Human and animal research indicates that oxytocin (OT) plays a key role in the cross-generational transmission of parental bonding, and human studies suggest that allelic variations on the oxytocin receptor gene ( OXTR ) and circulating OT levels interact with patterns of parental care to shape children's social-affiliative competencies. Yet, no study to date has tested the joint contribution of OT and parental care across three generations. Methods: The study included 345 participants comprising 115 family lines of grandmothers, mothers, and their infants. Salivary OT and allelic variations on the OXTR (rs53576 and rs2254298) and CD38 (rs3796863) single nucleotide polymorphisms (SNPs), which have been previously associated with parental bonding, were assessed in all participants. Parental care was measured from grandmothers to mothers and from mothers to their infants. Results: Mothers receiving parenting characterized by high overprotection from grandmothers showed more rejection toward their infants only when carrying the G allele on the OXTRrs53576 (AG/GG). These mothers of highly overprotective grandmothers also had lower oxytocin levels. Infants who were OXTRrs2254298 A carriers (AA/AG) and whose mothers reported more rejection toward their infants had higher oxytocin levels. Grandmothers receiving higher overprotection from great-grandmothers showed poorer parenting style compared to grandmothers experiencing lower parental overprotection only when carrying the OXTRrs2254298 GG genotype. Conclusions: Our findings are the first to demonstrate how genetic and peripheral markers on the oxytocin system interact with experienced parenting to shape bonding across three generations. Results have important implications for specifying the biological and behavioral determinants associated with the continuity of adaptive versus maladaptive patterns of attachment across generations.